Direct-Patterning ZnO Deposition by Atomic-Layer Additive Manufacturing Using a Safe and Economical Precursor - Stefanovic, Sonja; Gheshlaghi, Negar; Zanders, David; Kundrata, Ivan; Zhao, Baolin; Barr, Maissa; Halik, Marcus; Devi, Anjana; Bachmann, Julien (Small, 2023)
Area-selective atomic layer deposition (AS-ALD) is a bottom-up nanofabrication method delivering single atoms from a molecular precursor. AS-ALD enables self-aligned fabrication and outperforms lithography in terms of cost, resistance, and equipment prerequisites, but it requires pre-patterned substrates and is limited by insufficient selectivity and finite choice of substrates. These challenges are circumvented by direct patterning with atomic-layer additive manufacturing (ALAM) — a transfer of 3D-printing principles to atomic-layer manufacturing where a precursor supply nozzle enables direct patterning instead of blanket coating. The reduced precursor vapor consumption in ALAM as compared with ALD calls for the use of less volatile precursors by replacing diethylzinc used traditionally in ALD with bis(dimethylaminopropyl)zinc, Zn(DMP)2. The behavior of this novel ZnO ALAM process follows that of the corresponding ALD in terms of deposit quality and growth characteristics. The temperature window for self-limiting growth of stoichiometric, crystalline material is 200–250 °C. The growth rates are 0.9 Å per cycle in ALD (determined by spectroscopic ellipsometry) and 1.1 Å per pass in ALAM (imaging ellipsometry). The preferential crystal orientation increases with temperature, while energy-dispersive X-ray spectroscopic and XPS show that only intermediate temperatures deliver stoichiometric ZnO. A functional thin-film transistor is created from an ALAM-deposited ZnO line and characterized.
CRIS-Team Scopus Importer:2023-05-19
Keywords: additive manufacturing; atomic layer deposition; nanofabrication; sensors; zinc oxide

Sb2Se3Thin-Film Growth by Solution Atomic Layer Deposition - Koch, Vanessa; Charvot, Jaroslav; Cao, Yuanyuan; Hartmann, Claudia; Wilks, Regan G.; Kundrata, Ivan; Minguez Bacho, Ignacio; Gheshlaghi, Negar; Hoga, Felix; Stubhan, Tobias; Alex, Wiebke; Pokorný, Daniel; et al. (Chemistry of Materials, 2022)
We establish solution atomic layer deposition (sALD) for the controlled growth of pure Sb2Se3 thin films under mild conditions, namely, room temperature and atmospheric pressure. Upscaling this process yields Sb2Se3 thin films with high homogeneity over large-area (4″) substrates. Annealing of the initially amorphous material leads to highly crystalline and smooth Sb2Se3 thin films. Removing the constraints of thermal stability and sufficient volatility in sALD compared to traditional gas-phase ALD opens up a broad choice of precursors and allows us to examine a wide range of Se2- precursors, of which some exhibit facile synthetic routes and allow us to tune their reactivity for optimal experimental ease of use. Moreover, we demonstrate that the solvent used in sALD represents an additional, attractive tool to influence and tailor the reactivity at the liquid-solid interface between the precursors and the surface.
Created from Fastlane, Scopus look-up